The Effect of the Global Financial Crisis on Corporate Investment in Korea: From the Perspective of Costly External Finance - 정대희 (14098, 2015)
This paper examines the effect of the global financial crisis on corporate investment in Korea. Specifically, the crisis was considered to have possibly constrained firm-level investment as the negative shock to the credit supply dramatically unfolded. As